2017
DOI: 10.3390/ijerph14020145
|View full text |Cite
|
Sign up to set email alerts
|

Review and Extension of CO2-Based Methods to Determine Ventilation Rates with Application to School Classrooms

Abstract: The ventilation rate (VR) is a key parameter affecting indoor environmental quality (IEQ) and the energy consumption of buildings. This paper reviews the use of CO2 as a “natural” tracer gas for estimating VRs, focusing on applications in school classrooms. It provides details and guidance for the steady-state, build-up, decay and transient mass balance methods. An extension to the build-up method and an analysis of the post-exercise recovery period that can increase CO2 generation rates are presented. Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
173
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(176 citation statements)
references
References 43 publications
2
173
0
1
Order By: Relevance
“…Ventilation and air change rates (ACRs) were determined using CO 2 as a “natural” tracer gas, the steady-state mass balance model, field-measured CO 2 concentrations (20-min average from 5-sec measurements), observed occupancy (20-min average), measured salon volume, and CO2 emission rates for adult women (Batterman 2017). While the derived ACRs are approximate due to possible changes in occupancy, accuracy of the steady- state assumption, and the representativeness of measurements, ventilation parameters can provide key information to interpret the significance of emission sources and to support engineering controls to reduce exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Ventilation and air change rates (ACRs) were determined using CO 2 as a “natural” tracer gas, the steady-state mass balance model, field-measured CO 2 concentrations (20-min average from 5-sec measurements), observed occupancy (20-min average), measured salon volume, and CO2 emission rates for adult women (Batterman 2017). While the derived ACRs are approximate due to possible changes in occupancy, accuracy of the steady- state assumption, and the representativeness of measurements, ventilation parameters can provide key information to interpret the significance of emission sources and to support engineering controls to reduce exposure.…”
Section: Methodsmentioning
confidence: 99%
“…VRs were determined in each classroom using CO 2 as a tracer gas, classroom‐specific parameters (volume, grade‐level and occupancy), and four methods detailed elsewhere . The first used the “steady‐state” method, the maximum CO 2 concentration (assumed to be the steady‐state level) over the school day, the room volume, and the CO 2 generation rate for the 2 hour prior to the CO 2 peak.…”
Section: Methodsmentioning
confidence: 99%
“…Actual start and stop times were allowed to vary by ± 1 hour so as to maximize the concentration change over the period. The steady‐state concentration required by this method was determined using both the midpoint method and an implicit method that numerically solves the build‐up and steady‐state equations simultaneously . The implicit method improves stability and better addresses variable occupancy and non‐ideal shapes of the CO 2 build‐up curve.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural ventilation usually has a low investment and operational costs, while mechanical ventilation systems are more expensive and consume energy . Although there are several guidelines and standards by reputable organizations such as WHO (World Health Organization) and ASHRAE (American Society of Heating, Refrigerating and Air‐Condition Engineers), as well as national building codes, these standards are not always met: many studies from different countries have shown ventilation to be inadequate in a large proportion of classrooms . The reasons could be related to overcrowding in classrooms, as well as the type and condition of the school building and the ventilation system …”
Section: Introductionmentioning
confidence: 99%